Larval taxonomy of Macrothemis Hagen, 1868 (Odonata: Libellulidae), with descriptions of four larvae and a key to the fourteen known species - Salgado, Luiz Gustavo Vargas; Carvalho, Alcimar Do Lago; Pinto, Ângelo Parise (Zootaxa, 2013)
The ultimate larval stadia of Macrothemis declivata, M. hemichlora, M. imitans imitans and M. tenuis are described and illustrated for the first time, based on material from Brazil. Six of the most used keys to larvae of libellulid genera of the New World are evaluated with respect to the correct identification of the 27 known larvae of Macrothemis, Brechmorhoga, Gynothemis and Scapanea. Macrothemis species were wrongly identified in more than 50% of the trials, being keyed as Brechmorhoga, Gynothemis and even Dythemis. The genus Macrothemis and its relatives need to be revaluated and adequately diagnosed based on larvae. A key to the 14 known larvae of species currently included in Macrothemis is presented.